2022
DOI: 10.21203/rs.3.rs-1639208/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The associations between parity, abortion, and menopause status with the prevalence and incidence of thyroid dysfunctions: 12-year follow-up of Tehran Thyroid Study

Abstract: Background The effect of thyroid dysfunctions on the female reproductive system is well recognized. Although many studies pointed out the possible effect of female reproductive status alteration on thyroid function, there are too many contradictions to come up with an exact conclusion. This study aimed to investigate the associations of parity, abortion, and menopause status with the prevalence and incidence of thyroid dysfunctions. Methods From the Tehran Thyroid Study (TTS) population, 2191 euthyroid femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 7 , 8 , 10 , 13 , 24 , 26 A study conducted by Shariatzadeh et al has found a strong association between maternal thyroid dysfunction and abortions or miscarriages in Iran. 27 Thyroid dysfunctions are not only associated with abortions but are also responsible for several worse foetal and maternal outcomes. In this study raised serum TSH levels were significantly associated with the history of miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 , 10 , 13 , 24 , 26 A study conducted by Shariatzadeh et al has found a strong association between maternal thyroid dysfunction and abortions or miscarriages in Iran. 27 Thyroid dysfunctions are not only associated with abortions but are also responsible for several worse foetal and maternal outcomes. In this study raised serum TSH levels were significantly associated with the history of miscarriages.…”
Section: Discussionmentioning
confidence: 99%